Negative activation energy and dielectric signatures of excitons and excitonic Mott transitions in quantum confined laser structures - Bhunia, A.; Bansal, Kanika; Henini, M.; Alshammari, M.S.; Datta, Shouvik (AIP Publishing, 2016)
Mostly, optical spectroscopies are used to investigate the physics of excitons, whereas their electrical evidences are hardly explored. Here, we examined a forward bias activated differential capacitance response of GaInP/AlGaInP based multi-quantum well laser diodes to trace the presence of excitons using electrical measurements. Occurrence of “negative activation energy” after light emission is understood as thermodynamical signature of steady state excitonic population under intermediate range of carrier injections. Similar corroborative results are also observed in an InGaAs/GaAs quantum dot laser structure grown by molecular beam epitaxy. With increasing biases, the measured differential capacitance response slowly vanishes. This represents gradual Mott transition of an excitonic phase into an electron-hole plasma in a GaInP/AlGaInP laser diode. This is further substantiated by more and more exponentially looking shapes of high energy tails in electroluminescence spectra with increasing forward bias, which originates from a growing non-degenerate population of free electrons and holes. Such an experimental correlation between electrical and optical properties of excitons can be used to advance the next generation excitonic devices.